Optimization of the Cryogenic Light-Emitting Diodes for High-Performance Broadband Terahertz Upconversion Imaging - Bai, Peng; Zhang, Yueheng; Shen, Wenzhong; Yang, Ning; Chu, Weidong (Frontiers in Physics, 2021)
High performance THz imaging devices has drawn wide attention due to its significant application in variety of application fields. Recently, the up-conversion device based on the integrated homo-junction interfacial workfunction internal photoemission detector and light emitting diode (HIWIP-LED) has emerged as a promising candidate for broadband THz up-conversion pixelless imaging device. In this paper, systematical investigations on the cryogenic-temperature performances of LED part in HIWIP-LED devices, including electroluminescence (EL) spectra and the EL efficiency, have been carried out by elaborating the radiative recombination mechanism in the quantum well, internal quantum efficiency as well as the light extraction efficiency (LEE) both experimentally and theoretically. On this basis, we have further studied the operation mode of the HIWIP-LED and concluded that the light extraction efficiency could directly determine the up-conversion efficiency. A numerical simulation has been performed to optimize the light extraction efficiency. Numerical results show that device with the micro-lens geometry structure could significantly improve the LEE of the LED thereby in-creasing the up-conversion efficiency. An optimal up-conversion efficiency value of 0.12 W/W and minimum noise equivalent power (NEP) of 14 pW/Hz1/2 are achieved using the micro-lens structure together with anti-reflection coating. This work gives a precise description of cryogenic LED performance in the HIWIP-LED device and open the ways for optimization of the broadband HIWIP-LED THz up-conversion pixelless imaging device.